Proteomic Analysis of Lamellar Bodies Isolated from Amniotic Fluid: Implications for Function - Ridsdale, Ross; Lewis, David F.; Weaver, Timothy E.; Akinbi, Henry T. (American Journal of Perinatology, 2012)
Lamellar body count (LBC) in amniotic fluid is a well-established method for assessing fetal lung maturity. However, the biogenesis and function of lamellar bodies (LBs) secreted into the amniotic fluid have not been formally assessed. We purified LBs from amniotic fluids obtained from term gestation pregnancies that had been determined to have mature LBC. Using tandem mass spectrometry, we identified 122 unique proteins in the LB preparations from the amniotic fluids. There was minimal overlap between the proteins identified in amniotic fluid LB and those reported for human epidermis LB. In contrast, there was >40% concordance with the proteome of rat lung LBs despite species differences. Classification of the identified proteins into functional bins demonstrated that the preponderance of amniotic fluid LB proteins was associated with host defense or anti-inflammatory functions. These data suggest that amniotic fluid LBs are derived from lung secretions and may play an important role in innate host defense of the fetus.
Keywords: lamellar body; amniotic fluid; proteome; host defense